What Is Neuromarketing? - Bremer, Józef W. (Communication Today, 2025)
Neuromarketing is a relatively new domain of applied marketing research that studies the cognitive and affective reactions of consumers to marketing stimuli. It covers the overlap between neuroscience and research into consumer behavior, as well as advertising, marketing, and product design. Researchers make use of new technologies such as functional magnetic resonance imaging. In this article the author presents some basic information about the human brain and the new forms of neuroimaging technology available. Further on he analyzes three examples of neuromarketing research. Finally, the author comments on the ethical questions and the real contemporary significance of neuromarketing research.